Pilgrimage as Utopian performative for a post-colonial counterpublic - Llana, Jazmin Badong (Animo Repository, 2011)
Bigaa, Legazpi City, Albay, the cobacho dotoc is performed with a komedya enacting the search for the Holy Cross by Helena and Constantine. Nicanor Tiongson describes the komedya as ‘a play in verse [that] has conventions of stylized verse delivery, marching for entrances and exits, choreographed fighting and, very often, artifices to create magical effects on stage’(1999: 1). It is practised in many areas in the Philippines and is called by many names. In the town of Nabua, the community of Santa Elena (Baras), also performs the dotoc as the komedya of Helena’s search for the cross but in a longer form that includes fighting between Christians and Moors, which ends with the surrender of the non-Christians to Constantine. In the Canaman dotoc, the action is set at the end of the pilgrimage, when the cross had been found, and Helena’s entourage perform the lagaylay, a song and dance praise for the cross.